A promising marker for carotid artery disease: Monocyte to high-density lipoprotein ratio (MHR) - Mehmet Kirişçi (Sakarya Tıp Dergisi, 2020)
Objectives: The aim of our study was to evaluate the relation between monocyte/high-density lipoprotein(HDL) ratio value and carotid artery stenosis in patients who underwent carotid angiography.Methods: To our study, 94 participants were enrolled (68 patients, 26 healthy individuals) who attended the cardiovascular surgery policlinic and had carotid angiography in between January 2017 and June 2018. Participants were divided into two groups, who have carotid artery disease and who don't. Peripheral venous blood results, taken from all patients before angiography for hematologic examination, were evaluated. Groups were compared according to their monocyte/high-density lipoprotein(HDL)  values and other hematologic results.Results: Monocyte/high-density lipoprotein(HDL) ratio values were found to be higher in the group with a carotid artery disease compared to the group with a normal carotid angiography (72±10 ver 68±11  p=0.063). Yet again when the two groups were compared, there were differences with respect to existing hypertension, existing diabetes and gender (p=0.034, p=0.043, p=0.035 respectively).